JUVENILE IDIOPATHIC ARTHRITIS: CLINICAL PICTURE, DIAGNOSIS, TREATMENT - E. I. Alexeeva (Вопросы современной педиатрии)
The lecture presents current data on the development mechanisms, clinical features, diagnosis, prognosis and treatment of juvenile idiopathic arthritis.